The Effect of Climate Engineering on Strawberry Plant Growth in the Lowlands - Setiawan, Aa; Kartika, Ahmad Maulana; Wardika, Wardika (Jurnal Teknologi Terapan, 2018)
This research aims to study the effect of climate engineering on the growth of strawberry plants in the lowlands. This research was conducted in greenhouse media of 6 m2 wide and 2 m high with roof cover and wall of ultraviolet plastic with roof damper using straw. Types of strawberry plants that will be used are varieties of strawberries (Alpine) Red and White Mixed. The planting medium of strawberries uses a polybag placed on the shelf. The analysis discussed in this research is the analysis of temperature and humidity attainment and growth and development of strawberries. Temperature and humidity attainment is indicated with fixed temperature and humidity data of 17 0C – 20 0C and 80% - 90% Rh under all conditions. Strawberry growth analysis is indicated by increasing stolon size while development is indicated by a change in fruit form.The results showed that the greenhouse room during the day only able to reach an average temperature of 22 0C and 70% moisture. While in the morning and afternoon greenhouse space is able to reach the temperature and humidity of strawberry habitat. Using temperatures and humidity under the design, strawberry plants are still alive and well developed which is indicated by the addition of stolon length, the appearance of new shoots, fruit ripening, and the addition of strawberries.